Advances of Mass Rapid Transits Facilities in ASEAN Cities: A Review - Dullah H.; Khai W.J.; Ismail N.; Norhisham S.; Ramli M.Z.; Mohamad A.M.; Bakar M.F.A. (Springer Science and Business Media Deutschland GmbH, 2024)
The fact showed that public transportations necessity in this modern era now become more preferable, especially in developing countries. Some of the developing countries like Malaysia, Jakarta, and Thailand have been started a real step for that case. The practical use of the MRT is that it saves time in activities for workers and student. Malaysia has started first with MRT in 1995 followed by Philippines in 1999, Thailand (2003) and the last is Indonesia (2019). Public transportation like mass rapid transit (MRT) that has been built in several countries continues to do the evaluation and sustainable development to get the comfortable and safe transportation for MRT users. An essential dimension of rail travel is satisfaction with the level and quality of access to the station, which affects the overall satisfaction of the trip. The quality and level of accessibility are essential elements in explaining the use of trains. The focus of this review is public transportation facilities. Developing the transportation sector and developing countries are still carrying out their facilities. Various data related to MRT stations are collected from their particular website and made in written form from some of their videos. It is scarce and not easy to access literature about MRT stations by readers. The aim is to review, collect, and analyze data from three MRT stations, Bangkok, Jakarta, and Kuala Lumpur, based on the data available on the internet site. After the description, comparing stations through the table is the last step. One of them is the comparison of station elements which is a comparison of the overall MRT facilities between cities and others. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.